Rad51 supports triple negative breast cancer metastasis - Wiegmans, Adrian P (Impact Journals LLC, 2014)
In contrast to extensive studies on familial breast cancer, it is currently unclear whether defects in DNA double strand break (DSB) repair genes play a role in sporadic breast cancer development and progression. We performed analysis of immunohistochemistry in an independent cohort of 235 were sporadic breast tumours. This analysis suggested that RAD51 expression is increased during breast cancer progression and metastasis and an oncogenic role for RAD51 when deregulated. Subsequent knockdown of RAD51 repressed cancer cell migration in vitro and reduced primary tumor growth in a syngeneic mouse model in vivo. Loss of RAD51 also inhibited associated metastasis not only in syngeneic mice but human xenografts and changed the metastatic gene expression profile of cancer cells, consistent with inhibition of distant metastasis. This demonstrates for the first time a new function of RAD51 that may underlie the proclivity of patients with RAD51 overexpression to develop distant metastasis. RAD51 is a potential biomarker and attractive drug target for metastatic triple negative breast cancer, with the capability to extend the survival of patients, which is less than 6 months.